On Demand Load Balance Secure Routing Scheme For Mobile ADHOC Network (International Journal of Engineering and Computer Science, 2015)
Mobile Adhoc Network (MANET) is a special type of wireless network. It is characterized by dynamic topology (infrastructure less),multi-hop communication, limited resources (bandwidth, CPU, battery, etc.) and limited security. In this paper, we focus on the situation thatoccurs when specialized, sensitive data are sent to the Internet from MANET nodes. These special data types are especially susceptible to securityrisks such as information leak and data falsification. Therefore, it is necessary for such special data to be forwarded by a secure/trusted gatewaywhich is under control of a trusted network administrator. However, there can be multiple gateways deployed in a MANET, where the costineffectiveness makes it difficult for a network administrator to simultaneously manage every gateway. An optimum mechanism is used to selectan appropriate gateway out of the multiple gateways based on multiple node metrics: remaining energy and gateway load for interconnectedMobile Ad hoc Network (MANET) with infrastructure network. To choose an optimum gateway node, we use the Multiple Criteria DecisionMaking (MCDM) method called Simple Additive Weighting (SAW) for the optimum gateway node. SAW method calculates the weights ofgateway node by considering these two metrics. Node with the highest weight will be selected as a gateway. Because of the risk of forwardingspecial data through an unmaintained gateway, we propose a routing protocol, which allows a source node to have all data forwarded to theInternet through a trusted gateway. To achieve the desirable performance, we have implemented routing protocol called Dynamic MANET Ondemand (DYMO), which works in consideration of application data. Through simulations, we evaluate our protocol in comparison with theconventional DYMO protocol. We conclude through the simulation results that our protocol get better performance in terms of packet deliveryratio and transmission delay